2022
DOI: 10.1073/pnas.2117009119
|View full text |Cite
|
Sign up to set email alerts
|

Role of internal loop dynamics in antibiotic permeability of outer membrane porins

Abstract: Gram-negative bacteria pose a serious public health concern due to resistance to many antibiotics, caused by the low permeability of their outer membrane (OM). Effective antibiotics use porins in the OM to reach the interior of the cell; thus, understanding permeation properties of OM porins is instrumental to rationally develop broad-spectrum antibiotics. A functionally important feature of OM porins is undergoing open–closed transitions that modulate their transport properties. To characterize the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 87 publications
(123 reference statements)
4
28
0
Order By: Relevance
“…Possibly, the partially closed states correspond to intermediate size fluctuations of the current in single channel reading, while the closed state corresponds to short-lived and infrequent large amplitude fluctuations. Recently, a detailed Markov state model (MSM) study on OmpF reported large-scale backbone conformational changes in the L3 loop involved in the open to closed transition . A two-step mechanism was reported wherein E117 at the L3 tip interacts with the R42 on the opposite wall, followed by interactions of D121 with R132 and R82 leading to pore closure.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Possibly, the partially closed states correspond to intermediate size fluctuations of the current in single channel reading, while the closed state corresponds to short-lived and infrequent large amplitude fluctuations. Recently, a detailed Markov state model (MSM) study on OmpF reported large-scale backbone conformational changes in the L3 loop involved in the open to closed transition . A two-step mechanism was reported wherein E117 at the L3 tip interacts with the R42 on the opposite wall, followed by interactions of D121 with R132 and R82 leading to pore closure.…”
Section: Resultssupporting
confidence: 93%
“…This present results are consistent with previous experimental results on L3 loop tethering in ref , wherein two of the double mutants investigated (E117C–A333C and E117C–D312C) did not show any impairment of the voltage gating as compared to wild-type OmpF, indicating that the L3 tip at residue E117 remains stable in the event of a voltage-mediated pore closure. Interestingly, the MSM investigation by Vasan et al also reports an almost identical structural transition that involves motion of the D121 residue and its interaction with the R82 residue with a stable L3 tip as observed in the present study, albeit with a much lower likelihood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein modelling of the WT allele show that the NTC domain extends from the periplasm inwards into the porin and interacts with the inner loop 3 (L3), which traverses the upper region of the OmpU towards to the extracellular side. Domains analogous to NTC and L3 in other porins contribute to pore size and altered open and close conformation states [37, 62-67]. Given our findings, it is likely that the presence of the N-terminal coil contributes to a smaller pore size [37] in the WT allele leading to exclusion of bile molecules in contrast to the sensitive alleles.…”
Section: Discussionmentioning
confidence: 80%
“…However, unlike other third-generation cephalosporins, CP possesses a cephem nucleus substituted with a positively charged NMR, making it a zwitterion [ 2 ]. This zwitterionic property permits penetration of CP to Gram (+) bacteria's porin channels rapidly [ 10 , 11 ]. CP is used effectively to treat severe urinary and respiratory tract infections, as well as infections of the skin, soft tissues, and the women's reproductive tract among patients with febrile neutropenia.…”
Section: Introductionmentioning
confidence: 99%